Speaker Recognition Based On Auditory Impression: The Role Of Familiarity With The Speaker And Language - Šešum, Mia; Drljan, Bojana; Ivanović, Maja; Arsenić, Ivana (NBP. Nauka, bezbednosti, policija, 2025)
Speech is a fundamental means of interpersonal communication. Speaker identification based on voice and speech can be analysed through two perspectives, expert listening by trained phoneticians, for the purpose of forensic speaker identification and naïve listeners. Factors related to the success of identification often include prior familiarity with the speaker and the language they speak. The aim of the research was to determine the connection between speaker recognition based on the auditory impression of their voice and speech, prior familiarity with the speaker, and knowledge of the language they speak. The sample consisted of 218 female students. An instrument was specially designed for the purposes of this research. Prior familiarity with the speaker was only associated with recognizing female English speaker, while statistical analysis did not confirm the significance of recognizing speakers based on whether the listeners knew the foreign language of the speakers. Given that the research findings did not consistently support the hypothesis regarding the connection between prior familiarity with the speaker and the language they speak, and the success of speaker identification, it is necessary for future research to focus on examining the connection between recognizing speakers and the acoustic characteristics of their voice and speech.